Answer:
a = -12
b = 3
Explanation:
second term = a + 6b
to find the 5th term, notice the pattern (since this is a linear equation, each term increases by the same amount) and each term increases by 4b: 2b -> 6b -> 10b.
therefore, the 4th term would be a+14b and the 5th would be a+18b
so a + 6b = 8
and a + 18b = 44
u now have two simultaneous equations, which can be solved through substitution or elimination. I'm gonna use elimination because it's quicker in this case:
steps: (since the a would cancel out by subtracting, subtract then solve for b. divide by -12 on both sides to isolate the b)
now that u know the value of b, substitute it into an equation to solve for a:
a + 6b = 8
a + 6(3) = 8
a + 24 = 8
a = 8 - 24
a = -16
hope this helps!